2009
DOI: 10.1094/mpmi-22-9-1043
|View full text |Cite
|
Sign up to set email alerts
|

Partial Resistance ofMedicago truncatulatoAphanomyces euteichesIs Associated with Protection of the Root Stele and Is Controlled by a Major QTL Rich in Proteasome-Related Genes

Abstract: A pathosystem between Aphanomyces euteiches, the causal agent of pea root rot disease, and the model legume Medicago truncatula was developed to gain insights into mechanisms involved in resistance to this oomycete. The F83005.5 French accession and the A17-Jemalong reference line, susceptible and partially resistant, respectively, to A. euteiches, were selected for further cytological and genetic analyses. Microscopy analyses of thin root sections revealed that a major difference between the two inoculated li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(136 citation statements)
references
References 47 publications
4
132
0
Order By: Relevance
“…This result is in concordance to our previous microscope observations of phloroglucinol stained root sections which showed that lignin-like polymers accumulate around the pericycle in the A17 infected roots at 6 dpi (Djébali et al 2009). Lignification is a well known strategy that have developed many plants to prevent pathogen attack (Bhuiyan et al 2009).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is in concordance to our previous microscope observations of phloroglucinol stained root sections which showed that lignin-like polymers accumulate around the pericycle in the A17 infected roots at 6 dpi (Djébali et al 2009). Lignification is a well known strategy that have developed many plants to prevent pathogen attack (Bhuiyan et al 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, with the induced production of soluble phenolics in roots of the partially resistant line A17, presumably a reaction of oxidation by POX occurs which lead to the observed browning in A17 cortical root cells at 3 and 6 dpi. Browning of root tissues were observed in response to A. euteiches in three resistant lines DZA45.5, A17, and DZA315.16, whereas the roots tissues of the susceptible line F83005.5 showed a faint honey-gray colour (Djébali et al 2009). Resistance to several fungal plant pathogens has been ascribed to the accumulation of phenolic oxidation products that can inhibit pathogen development (Lebeda et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A major gene (RCT1) conferring resistance to anthracnose in alfalfa has been cloned in M. truncatula [80]. Similarly, QTL for resistance to A. euteiches [81,82], spring black stem and leaf spot [83] have been mapped in M. truncatula, but no verification of resistance in alfalfa has been documented. In addition to these disease resistances, QTL for nitrogen nutrition [84], flowering time [85] and aerial morphological characteristics [86] have been identified.…”
Section: Characteristics Of Alfalfa Genetic Linkage Mapsmentioning
confidence: 99%